Memory house The memory house collection - Crosby, Bette Lee (Port St. Lucie, FL Bent Pine, 2015)
"Ophelia Browne knows the answer is yes. She knows because she's been granted the unique gift of finding and caring for those forgotten memories. But now she's nearing ninety, and Browne women seldom live beyond ninety. Before time runs out Ophelia must find a successor. Someone who can take hold of the gifts and keep the memories from fading. When broken-hearted Annie Cross shows up on the doorstep of The Memory House Bed and Breakfast, Ophelia knows she is the one. The two women forge a bond of friendship as they sip magical dandelion tea and share stories. When Annie starts to sense the memories Ophelia is delighted, but then a thread of violence begins to unravel and Ophelia fears things have gone too far"--back cover.
Keywords: Female Friendship -- Fiction; Memory -- Fiction